Comparison of the oligosaccharide moieties of the major envelope glycoproteins of the subgroup A and subgroup B avian myeloblastosis-associated viruses. - Hunt, L A (1983)
The nature of the oligosaccharide chains of the major envelope glycoprotein, gp85, from avian myeloblastosis-associated viruses has been examined for the subgroup A and subgroup B viruses replicated in fibroblasts from the same chicken embryos. Pronase-digested glycopeptides from [3H]mannose- or [3H]glucosamine-labeled viruses were analyzed by the combined techniques of gel filtration, endo-beta-N-acetylglucosaminidase digestion, and concanavalin A affinity chromatography. The gp85 protein from these two viruses, and also from another subgroup A avian leukosis virus replicated in the same cells, contained a diverse array of asparagine-linked oligosaccharides of the acidic type [(sialic acid +/- galactose-N-acetylglucosamine)2-4-(mannose)3-N-acetylglucosamine2(+/- fucose)-asparagine], hybrid type (sialic acid +/- galactose-N-acetylglucosamine-(mannose)5,4-N-acetylglucosamine2-asparagine), and neutral type [(mannose)5-9-N-acetylglucosamine2-asparagine], with the more highly branched (tri or tetraantennary or both) acidic-type structures representing the predominant class of oligosaccharide. Minor differences were observed between the gp85 of the subgroup B versus subgroup A viruses.